Pengaruh Rekrutmen dan Promosi Jabatan Terhadap Kinerja Karyawan Pada PT. Bank Sinarmas Cabang Denpasar - Anak Agung Dwi Widyani; I Wayan Agus Permana Putra (Widya Manajemen, 2020)
This research was conducted based on differences in the focus of the discussion about recruitment and promotion of employee performance. Besides, there are also research problems about the decline in employee performance at PT Bank Sinarmas Denpasar Branch. This study aims to examine and analyze the effect of recruitment and promotion of position on employee performance. This research was conducted at PT Bank Sinarmas with a population and the sample of this study amounted to 87 respondents. All data obtained from the questionnaire distribution are feasible to use, then analyzed using SPSS 24.0. The results of the study give the meaning that recruitment has a positive and significant effect on employee performance; job promotion has a positive and significant effect on employee performance; recruitment and promotion have a positive and significant effect on employee performance. This research implies that recruitment can be improved by taking into account the basic indicators of recruitment, recruitment sources, and recruitment methods so that employee performance increases. Job promotion can be increased by taking into account indicators of employees who are loyal and with integrity, creativity, and initiative, more value than other employees, can provide solutions not only complaint and professional in working so that employee performance increases. Finally, employee performance can improve by taking into account indicators of quality, quantity, timeliness, effectiveness, and independence.